Pengaruh Struktur Modal dan Efisiensi Modal Kerja Terhadap Profitabilitas pada PT Aneka Tambang Tbk - Imelda; Puji Muniarty; Mukhlis (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of capital structure as measured by Debt to Equity Ratio (DER) and working capital efficiency as measured by Working Capital Turnover (WCTO) on profitability as measured by Return on Assets (ROA) at PT Aneka Tambang Tbk for the period 2015–2024. The study uses a quantitative approach with an associative research type. The data used are secondary data obtained from the annual financial statements of PT Aneka Tambang Tbk during the study period. The sample was determined using a purposive sampling technique and analyzed using multiple linear regression with the help of SPSS version 22. The results of the study indicate that capital structure and working capital efficiency have an important role in influencing company profitability. Optimal capital structure management can support an increase in the company's ability to generate profits, while the efficient use of working capital contributes to the smooth running of operational activities and improved financial performance. Together, these two variables provide a strong contribution in explaining changes in company profitability. These findings indicate that the success of PT Aneka Tambang Tbk in increasing profitability is inseparable from the company's ability to manage funding sources and utilize working capital effectively. Therefore, efficient management of capital structure and working capital needs to be a primary concern in efforts to improve the company's financial performance.